Empowering (e)ducators, inspiring learners: a cross-cultural exploration for interprofessional development through the lens of the Capability Approach - Pilar Gómez-Rey; Jorge Raúl Maradiaga; Francisco Fernández-Navarro; António Moreira Teixeira; Jose María Barroso-Tristán (Je-LKS: Journal of E-Learning and Knowledge Society)
The development of interprofessional capabilities has become a crucial strategy for addressing the multifaceted challenges of today’s increasingly interconnected and volatile workplace environment. This study examines Martha Nussbaum’s Capability Approach (CA) as a framework for cultivating key tangible outcomes - such as communication, critical reasoning, empathy, and collaboration - that are vital in the interprofessional context. Methodologically, the research adopts a quantitative approach to validate a life skills evaluation instrument and assess its effectiveness in diverse cultural settings. To achieve this, a Confirmatory Factor Analysis (CFA) was conducted on a dataset comprising 138 online instructors, complemented by statistical tests to identify significant cross-cultural differences in the prioritization and implementation of key skills. The main findings underscore the potential of e-learning practices, grounded in the CA framework, as a powerful tool for fostering the development of crucial capabilities essential for cultivating competent and well-rounded professional human beings. The findings of this study provided information on how to design teaching and learning for interprofessional development in the context of Pakistan, Portugal, Spain, and the United Kingdom.